EFEKTIFITAS KOMPRES HANGAT BASAH DAN KERING TERHADAP NYERI PUNGGUNG BAWAH PADA LANSIA DI WILAYAH KERJA PUSKESMAS TELEN KUTAI TIMUR KALIMANTAN TIMUR - Haryanti, Priyani; Juniarti, Gloria (STIKES Bethesda Yakkum, 2018)
Background: the elderly in the area of Talen health center with 229 people, there are 75 (32.75%) elderly suffer from low back pain.Wet and dry warm compress are nonpharmacological therapy in reducing pain. However the effectiveness between the two therapies is unknown. Objective: To determine the effectiveness of wet and dry warm compress on lower back pain in elderly at working area of Puskesmas Telen. ResearchMethod: It was a quasy experiment with pre and post test without control. Sampling was done by quota sampling technique, and the number of sample was 32 respondents divided into 2 groups. Data collection used Numeric Rating Scale. Mann Whitney statistical test. Results: The decrease in pain scale of warm dry compress 1,94 and wet 0,19 with P value 0,000 ? 0,05. Mann Whitney statistic test shows p value 0,481 ? 0,05. Conclusions: There is no difference in the effectiveness of warm and dry wet compress on lower back pain in elderly at working area of Puskesmas Telen. Suggestion: Further researchers may consider sampling technique using random to give equal opportunity for all respondents.Keywords: Elderly lower back pain - Warm and wet dry compress - Effectiveness